2013
DOI: 10.1039/c3cc37762h
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemically produced polydopamine nanocapsules with selective antimicrobial activity

Abstract: A facile, versatile, and one-pot sonochemical synthesis of polydopamine (PDA)-nanocapsules from dopamine is reported. The nanocapsules (227 ± 25 nm) can encapsulate hydrophobic substances while retaining the reactivity of PDA toward nucleophilic reactions, enabling facile surface modification for different applications. PDA nanocapsules are nontoxic to mammalian cells while Cu-containing PDA capsules demonstrate strong (99.9%) and rapid (15 min) bactericidal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 34 publications
3
61
1
Order By: Relevance
“…TheP DA coatings exhibited excellent antioxidant property and were able to efficiently protect the membrane surfaces.I na ddition, copper species show excellent antibacterial activity to av ariety of bacterial strains as well as Ag. [22] As mentioned above,some copper ions are still chelated with the PDAcoatings,which endow the membranes with good antibacterial performance toward E. coil and S. aureus (Figure 5d). It can be seen that about 97.4 %o f E. coil and 99.9 %o fS.…”
Section: Angewandte Chemiementioning
confidence: 86%
“…TheP DA coatings exhibited excellent antioxidant property and were able to efficiently protect the membrane surfaces.I na ddition, copper species show excellent antibacterial activity to av ariety of bacterial strains as well as Ag. [22] As mentioned above,some copper ions are still chelated with the PDAcoatings,which endow the membranes with good antibacterial performance toward E. coil and S. aureus (Figure 5d). It can be seen that about 97.4 %o f E. coil and 99.9 %o fS.…”
Section: Angewandte Chemiementioning
confidence: 86%
“…4 Copper has been widely used as an effective biocide for surface biofouling mitigation due to its strong antibacterial activity against a broad range of bacterial species and also low costs. 5 To date, many efforts have been devoted to incorporate copper nanoparticles 6 or their oxides/ionic forms, including copper hydroxide nanoparticles, 7 copper oxide nanoparticles 8 and copper ions, 9 onto substrate surfaces for biofouling resistance. For instance, polyethyleneimine (PEI)-coated copper nanoparticles (Cu NPs) were incorporated onto a reverse osmosis (RO) membrane surface through electrostatic interactions, leading to an 80−95% reduction in the number of attached live bacteria.…”
Section: Zongyao Zhou 12mentioning
confidence: 99%
“…PDA film has extraordinary adhesive properties for biomolecules . It is widely exposure that PDA‐coating surface can improve the stabilization of nanoparticles, enzymes and other materials . In especial, some reports confirm the activity and stability of protein are better after immobilized via covalently bond, physical adsorption and hydrogen bond interaction .…”
Section: Introductionmentioning
confidence: 99%
“…[18] It is widely exposure that PDA-coating surface can improve the stabilization of nanoparticles, [19][20][21] enzymes [22][23][24][25] and other materials. [26] In especial, some reports confirm the activity and stability of protein are better after immobilized via covalently bond, physical adsorption and hydrogen bond interaction. [27][28][29] Yuhong Renet al have revealed that with immobilized on PD-MNPs, pH and thermal stability of lipase have been enhanced compared to free lipase.…”
Section: Introductionmentioning
confidence: 99%